2012
DOI: 10.1371/journal.pone.0052049
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biological Properties of Electron Beam Melted Ti6Al4V Implant with Biomimetic Coating In Vitro and In Vivo

Abstract: BackgroundHigh strength porous titanium implants are widely used for the reconstruction of craniofacial defects because of their similar mechanical properties to those of bone. The recent introduction of electron beam melting (EBM) technique allows a direct digitally enabled fabrication of patient specific porous titanium implants, whereas both their in vitro and in vivo biological performance need further investigation.MethodsIn the present study, we fabricated porous Ti6Al4V implants with controlled porous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 43 publications
3
50
0
Order By: Relevance
“…However, Huiskes has maintained that with longer implant lifetimes, bone remodeling due to stress shielding will become an important issue making revision surgeries more difficult (46). The EBM-processed scaffolds described here have mechanical properties within the range of cortical and cancellous bone (21) and is in concurrence with recent observations by Li et al (50). Porous titanium scaffolds could be effective for use in physiologically optimized load bearing and non-load bearing bone replacement implants.…”
Section: Discussionsupporting
confidence: 91%
“…However, Huiskes has maintained that with longer implant lifetimes, bone remodeling due to stress shielding will become an important issue making revision surgeries more difficult (46). The EBM-processed scaffolds described here have mechanical properties within the range of cortical and cancellous bone (21) and is in concurrence with recent observations by Li et al (50). Porous titanium scaffolds could be effective for use in physiologically optimized load bearing and non-load bearing bone replacement implants.…”
Section: Discussionsupporting
confidence: 91%
“…In vivo histological analysis has obtained a rapid in‐growth of bone tissue from calvarial margins toward the center of bone defect in 12 weeks. They found that the bone in‐growth within the implant with or without apatite coating was quite similar, which means the implants can be directly used without surface modifications …”
Section: Design Considerations For Orthopaedic Implants Using Additivmentioning
confidence: 99%
“…In this regard, a number of titanium alloys were developed for biomedical applications. Ti-6Al-4V alloy, originally developed as an aeronautical material, has been tested as a replacement for pure Ti, because of its higher strength with sufficient corrosion resistance [61]. However, extensive investigations have shown that the release of V ion from the Ti-6Al-4V alloy to the human body might cause long-term health problems, such as peripheral neuropathy, and osteomalacia diseases [62].…”
Section: Discussionmentioning
confidence: 99%